AB0898 Biomarker for spondyloarthritis: Autoantibodies against class II-associated invariant chain peptide (clip). (23rd January 2014) - Baerlecken, N.T.; Nothdorft, S.; Stummvoll, G.H.; Sieper, J.; Rudwaleit, M.; Reuter, S.; Matthias, T.; Schmidt, R.E.; Witte, T.
Abstract : Background: Spondyloarthritis (SpA) is relatively common inflammatory disorder with a frequency of 1-2% in the European population (1). Establishing the diagnosis however may be difficult, since abnormalities in conventional X-ray develop with a latency of several years and so far only HLA-B27 has been established as a laboratory marker of the disorders (2). Besides MRI, there are no sufficient tools for the early diagnosis of SpA (3). Objectives: The goal of our study therefore was to identify new autoantibodies as markers of SpA. Methods: As a screening procedure, we used protein array technology for detection of possible new autoantigens in SpA. Sera of patients with SpA without peripheral manifestation (n=5) and other diseases as controls (n=45), were studied. In the second step, the results of the protein array were confirmed by ELISA using commercially available recombinant antigens (Abnova, Taiwan and Abcam, UK) and new synthetic derived peptides (Biomatik, USA). Considering the sensitivity and specificity, we developed an ELISA with synthetic peptide Class II-associated invariant chain peptide (CLIP) in cooperation with AESKU.Diagnostics (Wendelsheim, Germany). The sera for the ELISA were obtained from 198 SpA patients visiting the rheumatological outpatients and inpatients clinics, 80 rheumatoid arthritis (RA), 40 systemic lupus erythematosus patients (SLE), 40 human immunodeficiency virus (HIV) infected patients with elevated viral load and 100 blood donors. All donors provided informed consent for the study which was approved by our local ethical committee (project number 4928). Results: Using the protein array, we detected IgG antibodies against CD74 in 4/5 SpA sera, but only in 1/45 controls. After we tested different different CD74 proteins as antigens in ELISAs, we chosed a peptide which includes the CLIP within the CD74 protein. Of the SpA patients with disease onset less than 1-6 months ago 24/24 (100%), less than 7-12 months 32/34 (94%) were positive for IgG autoantibodies. After 20yrs, the frequency of IgG autoantibodies against CD74 decreased to 65%. 141/196 (71%) of all SpA patients showed positivity for IgG autoantibodies against CLIP. In the further control groups, the prevalence of IgG autoantibodies against CLIP was 14/80 (17.5%) in RA, 5/40 (12.5%) in SLE, 1/40 (2.5%) in HIV and 0/100 (0%) in blood donors . Conclusions: Considering their specifity and sensitivity, antibodies against CLIP will be an useful addition to our diagnostic tools for SpA in the future. References: Braun J, Bollow M, Remlinger G. Prevalence of Spondylarthropathies in HLA-B27 positive and negative blood donors. Arthritis Rheum 1998;41:58–67 Dincer U, Cakar E, Kiralp MZ, Dursun H. Diagnosis delay in patients with ankylosing spondylitis: possible reasons and proposals for new diagnostic criteria. Clin Rheumatol. 2008;27:457-62. Bennett AN, Rehman A, Hensor EM, Marzo-Ortega H, Emery P, McGonagle D, The fatty Romanus lesion: a non-inflammatory spinal MRI lesion specific for axial spondyloarthropathy. Ann Rheum Dis. 2010;69:891-4. Disclosure of Interest: None Declared